Exploring Latent Class Profiles of Mathematics Performance: Insights from PISA 2022 Using Growth Mindset Indicators and Group Comparison Analysis - Chavez, Von Lorenz A. (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study investigates the influence of a growth mindset on Filipino students’ mathematics performance as assessed in the PISA 2022 survey. The research aims to identify distinct latent class profiles based on growth mindset indicators and to explore their relationship with mathematics achievement. Methodology: Data from 6,791 Filipino students who participated in PISA 2022 were analyzed. Latent Class Analysis (LCA) was employed to classify students into distinct mindset profiles, while Analysis of Variance (ANOVA) assessed differences in mathematics performance across these groups. Tukey’s post hoc analysis was used to examine pairwise differences further. Main Findings: Based on the data, three distinct latent classes were identified among Filipino learners: Limitation Acceptors (50%), Optimistic Learners (17%), and Mindset Explorers (33%). Optimistic Learners, who exhibited a strong growth mindset and disagreed with statements endorsing fixed intelligence, achieved the highest average scores in mathematics. ANOVA results confirmed significant differences in mathematics performance among these three groups. Tukey’s post hoc analysis further revealed that Optimistic Learners significantly outperformed Limitation Acceptors and Mindset Explorers, while no significant performance difference was found between Limitation Acceptors and Mindset Explorers. Novelty/Originality of this study: These findings highlight the critical role of a growth mindset in shaping academic achievement and suggest that fostering growth-oriented beliefs could enhance mathematics performance. This study provides actionable insights for educators and policymakers, emphasizing the need for targeted interventions to cultivate positive beliefs about intelligence among students.